Edukasi Peningkatan Kesehatan Lingkungan dan Higiene Perorangan Santri Ponpes Indhotun Nasyi'in Lamongan - Sulistyorini, Lilis; Dwiyanti, Endang; Mahmudah, Mahmudah; Haqi, Dani Nasirul; Arfiani, Novi Dian (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Environmental health and personal hygiene are important aspects in improving the quality of life of the community. Indhotun Nasyi'in Islamic Boarding School in Lamongan is an Islamic educational institution that functions to build the character and awareness of students about the importance of environmental health and personal hygiene. Therefore, it is necessary to conduct education to increase students' awareness and knowledge about environmental sanitation and personal hygiene. An educational and participatory approach, using posters, was used to increase students' knowledge. The average age of participants was 14.46±1.456 years, 63% were female, 67% were students in grades 7 and 8, and 84% were from Lamongan. There was a significant increase in students' knowledge (p-value 0.001) after receiving education. The average score of students increased, from 8.22 in the pre-test to 9.04 in the post-test. This program also successfully identified that most students did not understand the concept of waste management based on the 4R principle, namely Reduce, Reuse, Recycle, and Replace. Therefore, the community service team plans follow-up activities to develop habits that can be applied in the students' daily lives.